Manual composite layup & spray up - Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2005)
Follows each process of manual composite layup and spray up, detailing each step from molds preparation through to the curing of finished layups and spray ups
Title from title screen
DVD format
Keywords: Reinforced plastics; Composite materials